Effects of riluzole on psychiatric disorders with anxiety or fear as primary symptoms: A systematic review - Yoshitaka Kawashima; Misa Yamada; Hiroki Furuie; Hiroshi Kuniishi; Kie Akagi; Tomoko Kawashima; Takamasa Noda; Mitsuhiko Yamada (Wiley, 2023)
Abstract Aim Previous behavioral pharmacology studies involving rodents suggested riluzole had potential to be an ideal psychotropic drug for psychiatric disorders with anxiety or fear as primary symptoms. Several clinical studies have recently been conducted. The purpose of this study was to gather information about the efficacy and tolerability of riluzole for patients with those symptoms. Methods We searched PubMed, PsycINFO, CINAHL, EMBASE, and the Cochrane database from inception until April 2021, and performed manual searches for additional relevant articles. This review included: (1) studies involving participants that were patients with generalized anxiety disorder (GAD), social anxiety disorder, panic disorder, obsessive‐compulsive disorder (OCD), posttraumatic stress disorder (PTSD), acute stress disorder, or phobias; and (2) randomized controlled trials (RCTs) or intervention studies (e.g., single arm trials) examining the effects and safety of riluzole. Results Of the 795 identified articles, four RCTs, one RCT subgroup‐analysis, and three open‐label trials without control groups met the inclusion criteria. Most trials evaluated the efficacy of riluzole as an augmentation therapy with selective serotonin reuptake inhibitors and other antidepressants for PTSD, OCD, or GAD. However, there was insufficient evidence to confirm the effects of riluzole for patients with these psychiatric disorders. Most trials demonstrated adequate study quality. Conclusions This review found insufficient evidence to confirm the effects of riluzole for psychiatric disorders with anxiety or fear as primary symptoms. It would be worthwhile to conduct studies that incorporate novel perspectives, such as examining the efficacy of riluzole as a concomitant medication for psychotherapy.